Laboratory manual : Stern's introductory plant biology - Bidlack, James E. (New York : McGraw Hill Education, 2008)
This laboratory manual assumes no previous knowledge of the biological sciences on the part of the student. It is designed for use in a one-semester or one-quarter introductory course in plant biology and shorter introductory botany courses open to both nonmajors and majors.
The microscope -- The cell -- Mitosis -- Roots -- Stems -- Leaves -- Plant propagation -- Cell components and products -- Diffusion, growth, and hormones -- Photosynthesis -- Water in plants; respiration; digestion -- Meiosis and alternation of generations -- Domain and kingdom survey -- Domains (kingdoms) archaea and bacteria; kingdom fungi (mycota) -- Kingdom plantae: bryophytes and ferns -- Kingdom plantae: gymnosperms -- Kingdom plantae: angiosperms (flowering plants -- phylum magnoliophyta) -- Fruits, spices, survival plants, and poisonous plants -- Ecology -- Genetics.